Analisis Kesalahan Sintaksis pada Teks Deskripsi Siswa Kelas VII SMPK St. Isidorus Lewotala Tahun Ajaran 2022/2023 - Maria Peria Kelen, Sofiana; Pande, Rikardus; Wai Lawet, Pilipus (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This article aims to describe the types of syntactic errors in the descriptivetext of class VII SMPK St. Isidorus Lewotala. The problem discussed is what are the types of syntactic errors in the description text of class VII students of SMPK St. Isidorus Lewotala. Language errors are basically caused by the person who uses the language in question, not the language he uses. The theory used is the theory of language errors put forward by Setyawati with three possible causes of language errors, namely being influenced by the language that was previously mastered, the language user's lack of understanding of the language he uses, and language teaching that is inappropriate or imperfect. The method used is a qualitative descriptive method and the approach used is a qualitative approach. The source of the data in this study were class VII students of SMPK St. Isidorus Lewotala. The data collected is in the form of phrases, sentences which are included in the types of syntax errors in the descriptive text. Data collection techniques were carried out using observation and documentation techniques. Data analysis was carried out by identifying errors, classifying errors, presenting data and drawing conclusions. This research was conducted at SMPK St. Isidorus Lewotala, Lewotala village, Lewolema sub-district, East Flores district. The results of this study indicate that there are four types of syntactic errors in the field of phrases consisting of: 1) inappropriate use of prepositions, 2) inappropriate wording, 3) excessive use of elements, and 4) double pluralization. There are five types of syntactic errors in the field of sentences, including: 1) sentences without a subject, 2) stump sentences, 3) excessive use of conjunctions, 4) use of foreign terms, and 5) use of unnecessary question words.